Antimicrobial activity of essential oils from Benin on five oral germs: Test of mouth baths. - BABA-MOUSSA, FARID; ADJANOHOUN, Adolphe; ATTAKPA, S. EUGÈNE; Kpavodé, Lysette; GBENOU, Joachim; Koffi, Akpagana; KOTCHONI, SIMEON; SEZAN, ALPHONSE; TOUKOUROU, FATIOU; Baba- Moussa, Lamine (My University, 2012)
In Beninese pharmacopeia, many plants are considered as having some an-timicrobial properties. The first objective of this study is, to evaluate the an-timicrobial activity of three essential oils on five bucco-dental germs and to carry out mouthwash with essential oils. The second objective is to deter-mine their Inhibiting Minimal Concentrations (IMC), Bactericidal Minimal Concentrations (BMC) and chemical compositions. The results of this work revealed that the Inhibiting Minimal Concentrations (IMC’s) of the oils vary between 0,078 and 2,50 mg/Ml. The mouth wash carried out at 2°/°° essen-tial oil was efficient on the five germs with dilutions between ½ and 1/16. The chemical analysis of the most active essential oil shows the presence of: estragole (84,98%), geranial (34,92%), neral (30,75%), para-cymene (21,89%), 1,8-cineole (10,09%) et thymol (8,46%).The most active essential oils can be used in aromatherapy to improve health and the well-being.
Keywords: essential oils; Inhibiting Minimal Concentration; Bactericidal Minimal Concentration; mouthwash.